PENGECAMBAHAN BIJI DAN PERTUMBUHAN SEEDLING PHALAENOPSIS HIBRIDA IN VITRO PADA DUA MEDIA DASAR DENGAN ATAU TANPA ARANG AKTIF - Yusnita, Yusnita; Handayani, Yivista (JURNAL AGROTROPIKA, 2011)
Two consecutive experiments that aimed to investigate effects of basal media and activated charcoal (AC) on (1) in vitro seed germination and in vitro seedling growth of Phalaenopsis hybrids were conducted. Phalaenopsis seeds taken from sterilized ripe pods were sown aseptically on MS or Growmore medium with or without 2 g/l AC, then the protocorms produced were counted after two months of culture. The same combinations of basal media and AC were used to grow protocorms produced from previous experiment for another two months, then the growth of seedlings were measured. The two experiments were arranged in a completely randomized design with three replicates. Each experimental unit consisted of four culture bottles each of which contained the same amount of seeds (in the first experiment) or five protocorms (in the second experiment). Data were subjected to analysis of vari-ance and if there was any significant F result (s), the means were separated using least significant difference at P? 0.05. Results of the first experiment showed that for in vitro germination of Phalaenopsis seeds, Grow-more medium produced significantly higher number of protocorms campared to MS, and addition of AC in both media significantly decreased the number of protocorms. Results of the second experiment showed that for in vitro growth of Phalaenopsis seedlings, either MS or Growmore medium resulted in the same seedling growth. However, addition of 2 g/l AC in the media significantly increased seedling growth as shown by higher values in plant height, number and length of roots as well as seedling fresh weight. So, it was concluded that Growmore medium was better than MS for in vitro seed germination and the same as MS for seedling growth of Phalaenopsis. The addition of AC in the medium was inhibitory for seed germination, but stimulatory for seedling growth. Keywords: activated charcoal, basal media, Phalaenopsis, seed germination, seedling growth.